2012
DOI: 10.1016/j.rppneu.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome da Apneia-Hipopneia do Sono e Síndrome Coronária Aguda – Uma associação a não esquecer

Abstract: In our study, we found a high prevalence of SAHS in patients who were admitted to the CCU with ACS (43.1%). These results support the need for SAHS screening in patients who are hospitalized with ACS. The SST may have a role in the screening of SAHS in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Therefore, this value did not seem to be a determining factor in the diagnosis of SA in these patients. The limitations of ESS are known in cardiovascular patients and the existence of patients with severe SA without excessive sleepiness is controversial [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this value did not seem to be a determining factor in the diagnosis of SA in these patients. The limitations of ESS are known in cardiovascular patients and the existence of patients with severe SA without excessive sleepiness is controversial [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SA in patients with CAD was higher than in normal population, as stated by numerous studies, and was in range or higher than in our study. The studies reported a wide range of prevalence, ranging from 26% to 66%, partially explained by the different value of AHI used to establish the diagnosis of SA in the different studies [ 3 , 5 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of ESS are known in CV patients and the existence of patients with severe SA without excessive sleepiness is controversial. 47 , 48 An independent association between CV morbidity and breathing disorders in sleep was reported even for patients with SA within the normal range of AHI (1–10 events/h). 26 Although it is not feasible to refer all patients with CAD for a polysomnographic study in a sleep laboratory, some form of screening for SDB is needed.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies evaluated obstructive sleep apnea and reported rates of: 47%, 43.1%, 76%, and 63% respectively, 3033 when using either the Berlin Questionnaire 30, 32 or portable systems. 31, 33 Van den Broecke et al performed a remotely conducted sleep study using a tele-monitoring system to measure CSR and PB. 34 …”
Section: Discussionmentioning
confidence: 99%